Differences in time of start reaction and achieved result in the sprint disciplines in the finals of the Olympic Games in London - Pavlovic, R.; Idrizovic, K.; Vrcic, M.; Mosurovic, M. (Sports Science and Health, 2014)
In the sprint events a very important place take the start and start acceleration which is largely generated by the final score. Depending on the appropriate individual morphological dimension, especially motor and functional abilities of competitors, good possibility to implement these parameters is certain. However, despite the excellent results they achieve, differences in these two parameters are evident, which in terms of the final result has a certain effect. The aim of this study was to determine the differences in the starting reaction time and results in the sprint events of the finalists at the Olympic Games in London in 2012. The results from the finalists (24 male) and 24 (women) participants were analysed that participated in the final races in the 100m, 200m and 400m. The evaluation of starting reaction time (ms) and results in a sprint (s) based on the reports that were officially published by the International Association of Athletics Federations (IAAF). The results of the analysis of t-test showed statistically significant differences in response time for female athletes in the disciplines of running 100m and 400m (t=-3.220; p<0,01) as well as for the 200m and 400m events (t =-2.550; p<0,05) unlike male finalists for which there were no statistically significant differences. Also, in the same disciplines between the sexes there were no statistically significant differences, while they are evident in the results achieved in the disciplines of 100m (t= -2.842; p<0,05), 200 (t= -11.526; p<0,01) and 400 (t= -27.019; p<0,01).